The role of multislice computed tomography (MSCT) in the detection of blunt traumatic intra abdominal injury: our experience in Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang. - Radhiana, Hassan; Azian, Abd Aziz; Mubarak, Mohd Yusof; Saot, Azlin; Mohd Amran, Abdul Rashid; Ab Rahman, Jamalludin (Malaysian Medical Association, 2012)
Multislice computed tomography (MSCT) is the imaging modality of choice in assessing clinically stable patients with blunt abdominal trauma. This study assessed the role of MSCT in the detection of intra abdominal injury caused by blunt trauma in our centre within a two-year-period (2008-2009). A total of 151 patients had MSCT abdomen for blunt abdominal trauma within this study period. Positive scan were seen in 126 patients (83.4%). Out of these positive scans, liver, spleen and renal injuries were seen in 42.1% (n = 53), 34.9% (n = 44) and 30.0% (n = 34) of cases respectively. Laparotomies were performed in 45 patients. Out of these 45 laparotomies, 10 patients had surgically significant injuries that were missed on CT scan findings. The injuries were bowel perforation (n = 4), serosal tear of bowel (n = 1), mesenteric injuries with active haemorrhage (n=3), spleen injury (n = 1) and liver injury (n = 1).